Eating disorder pathology in elite adolescent athletes - Giel, K. E.; Hermann-Werner, A.; Mayer, J.; Diehl, K.; Schneider, S.; Thiel, A.; Zipfel, S. (International Journal of Eating Disorders, 2016)
Objective: We aimed to investigate eating disorder pathology in German elite adolescent athletes. Evidence suggests that eating disorder pathology is more common in adult elite sports, especially in female athletes and in sports emphasizing leanness. There is a scarcity of studies in elite adolescent athletes who are in a vulnerable developmental stage and are affected by general as well as sport-specific risk factors.